The relationship between bullying and self esteem in adolescents in class VII of SMPN 7 Palangka Raya - Priskila, Eva; Ibrahim, Dwi Agustin Faruk; Sari, Ni Wayan Anita (Institute Of Computer Science (IOCS), 2025)
Bullying is defined as any deliberate, persistent, and harmful kind of intimidation or aggressive behavior directed at others by a person or group of individuals who are stronger or more powerful. A person's evaluation of themselves, both favorably and unfavorably overall, is based on their level of self-esteem. Bullying behavior can have an impact on how self-esteem develops, leading to teenagers having low self-esteem. In today's schools, it is common for teenagers to be shy, lack confidence, or remove themselves from their friends since they have been teased by them. There are 10 male students and 7 female students from class VII who feel inferior because they are often teased by their friends, some of them also admit that they often call their friends rude names (animal names). In order to examine the connection between bullying and self-esteem in SMPN 7 Palangka Raya adolescents in class VII, this study used a cross-sectional strategy and a correlational study design. 151 pupils in class VII of SMPN 7 Palangka Raya made up the study's population, while 33 respondents made up the sample. At the end, the p value is 0.000 <0.05 when the significant value is 0.05 using the Chi square test (0.000). In order to support the H1 hypothesis, adolescents in class VII of SMPN 7 Palangka Raya exhibit a substantial correlation between bullying and self-esteem. Conclusion: The study's findings show a strong correlation between bullying and self-esteem among teenagers in SMPN 7 Palangka Raya's seventh grade.